First case of postmortem study in a patient vaccinated against SARS-CoV-2. (June 2021) - Hansen, Torsten; Titze, Ulf; Kulamadayil-Heidenreich, Nidhi Su Ann; Glombitza, Sabine; Tebbe, Johannes Josef; Röcken, Christoph; Schulz, Birte; Weise, Michael; Wilkens, Ludwig
Highlights: We report on a patient with a single dose of vaccine against SARS-CoV-2. He developed relevant serum titer levels but died 4 weeks later. By postmortem molecular mapping, we found viral RNA in nearly all organs examined. However, we did not observe any characteristic morphological features of COVID-19. Immunogenicity might be elicited, while sterile immunity was not established. Abstract: A previously symptomless 86-year-old man received the first dose of the BNT162b2 mRNA COVID-19 vaccine. He died 4 weeks later from acute renal and respiratory failure. Although he did not present with any COVID-19-specific symptoms, he tested positive for SARS-CoV-2 before he died. Spike protein (S1) antigen-binding showed significant levels for immunoglobulin (Ig) G, while nucleocapsid IgG/IgM was not elicited. Acute bronchopneumonia and tubular failure were assigned as the cause of death at autopsy; however, we did not observe any characteristic morphological features of COVID-19. Postmortem molecular mapping by real-time polymerase chain reaction revealed relevant SARS-CoV-2 cycle threshold values in all organs examined (oropharynx, olfactory mucosa, trachea, lungs, heart, kidney and cerebrum) except for the liver and olfactory bulb. These results might suggest that the first vaccination induces immunogenicity but not sterile immunity.